2020
DOI: 10.1108/acmm-03-2019-2092
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion behavior of heat-treated and cryorolled Al 5052 alloys in different chloride ion concentrations

Abstract: Purpose This paper aims to investigate the corrosion behaviour of heat-treated and cryorolled Al 5052 alloys in different Cl− ion concentrations. Design/methodology/approach NaCl solutions with concentrations of 0, 0.5, 3.5 and 5.5 per cent were selected. Samples were subjected to pre-heat treatment (annealing at 300 °C and solution treatment at 540 °C) and cryorolling up to 30 per cent reduction before undergoing corrosion tests. The corrosion behaviour of the samples was then investigated by potentiodynami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Figure 6 and Table 3 show that the corrosion current (icorr) decreases with the increment of the CEC pass number. This can be due to the facile formation of a protective oxide layer on the refined It was reported that Al5052 alloy has a favorable corrosion resistance mainly due to the fabrication of a protective surface oxide layer and has a low corrosion rate, especially in saline solutions and marine applications [51]. As it can be inferred from Figure 6, the corrosion resistance of Al5052 alloy is further promoted by the application of the CEC method.…”
Section: Corrosion Resistancementioning
confidence: 95%
“…Figure 6 and Table 3 show that the corrosion current (icorr) decreases with the increment of the CEC pass number. This can be due to the facile formation of a protective oxide layer on the refined It was reported that Al5052 alloy has a favorable corrosion resistance mainly due to the fabrication of a protective surface oxide layer and has a low corrosion rate, especially in saline solutions and marine applications [51]. As it can be inferred from Figure 6, the corrosion resistance of Al5052 alloy is further promoted by the application of the CEC method.…”
Section: Corrosion Resistancementioning
confidence: 95%